(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Galega officinalis L. is a promising medicinal plant. Galega officinalis contains alkaloids, glycosides, carbohydrates, proteins, tannins, saponins, phenylcarboxylic acids, flavonoids, triterpenes and etc. Preparations of Galega officinalis have hypoglycemic activity and have a complex effect on the body. Despite the large number of medicinal properties, Galega officinalis is poisonous, as a result of which it has certain contraindications for use.